The Attenuating Effect of Low-Intensity Pulsed Ultrasound on Hypoxia-Induced Rat Chondrocyte Damage in TMJ Osteoarthritis Based on TMT Labeling Quantitative Proteomic Analysis - Du, Sa; Liang, Chao; Sun, Yujie; Ma, Bowen; Gao, Wenmo; Geng, Wei (Frontiers in Pharmacology, 2021)
Temporomandibular joint osteoarthritis (TMJOA) is a degenerative disease with a complex and multifactorial etiology. An increased intrajoint pressure or weakened penetration can exacerbate the hypoxic state of the condylar cartilage microenvironment. Our group previously simulated the hypoxic environment of TMJOA in vitro. Low-intensity pulsed ultrasound (LIPUS) stimulation attenuates chondrocyte matrix degradation via a hypoxia-inducible factor (HIF) pathway-associated mechanism, but the mode of action of LIPUS is currently poorly understood. Moreover, most recent studies investigated the pathological mechanisms of osteoarthritis, but no biomarkers have been established for assessing the therapeutic effect of LIPUS on TMJOA with high specificity, which results in a lack of guidance regarding clinical application. Here, tandem mass tag (TMT)-based quantitative proteomic technology was used to comprehensively screen the molecular targets and pathways affected by the action of LIPUS on chondrocytes under hypoxic conditions. A bioinformatic analysis identified 902 and 131 differentially expressed proteins (DEPs) in the < 1% oxygen treatment group compared with the control group and in the < 1% oxygen + LIPUS stimulation group compared with the < 1% oxygen treatment group, respectively. The DEPs were analyzed by gene ontology (GO), KEGG pathway and protein-protein interaction (PPI) network analyses. By acting on extracellular matrix (ECM)-associated proteins, LIPUS increases energy production and activates the FAK signaling pathway to regulate cell biological behaviors. DEPs of interest were selected to verify the reliability of the proteomic results. In addition, this experiment demonstrated that LIPUS could upregulate chondrogenic factors (such as Sox9, Collagen Ⅱ and Aggrecan) and increase the mucin sulfate content. Moreover, LIPUS reduced the hydrolytic degradation of the ECM by decreasing the MMP3/TIMP1 ratio and vascularization by downregulating VEGF. Interestingly, LIPUS improved the migration ability of chondrocytes. In summary, LIPUS can regulate complex biological processes in chondrocytes under hypoxic conditions and alter the expression of many functional proteins, which results in reductions in hypoxia-induced chondrocyte damage. ECM proteins such as thrombospondin4, thrombospondin1, IL1RL1, and tissue inhibitors of metalloproteinase 1 play a central role and can be used as specific biomarkers determining the efficacy of LIPUS and viable clinical therapeutic targets of TMJOA.